Tri-state single-phase integrated inverters with input to output power decoupling control - De Brito, Moacyr A.G [UNESP]; Junior, Luigi G. [UNESP]; Sampaio, Leonardo P. [UNESP]; Canesin, Carlos A. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Researches on control for power electronics have looked for original solutions in order to advance renewable resources feasibility, specially the photovoltaic (PV). In this context, for PV renewable energy source the usage of compact, high efficiency, low cost and reliable converters are very attractive. In this context, two improved simplified converters, namely Tri-state Boost and Tri-state Buck-Boost integrated single-phase inverters, are achieved with the presented Tri-state modulation and control schemes, which guarantees the input to output power decoupling control. This feature enhances the field of single-phase PV inverters once the energy storage is mainly inductive. The main features of the proposal are confirmed with some simulations and experimental results. © 2012 IEEE.
Keywords: Inductive Power Decoupling; Integrated Inverters; Single-Stage Converters; Tri-State Modulation and Control; Buck-boost; Control schemes; Decoupling controls; Integrated inverter; Low costs; Output power; Photovoltaic; PV inverter; Renewable energy source; Renewable resource; Single stage converters; Single-phase inverters; Modulation; Renewable energy resources; Power electronics